Whole-Body CT in Multiple Trauma Patients: Clinically Adapted Usage of Differently Weighted CT Protocols - Reske, Stefan Ulrich; Braunschweig, Rainer; Reske, Andreas Wolfgang; Loose, Reinhard; Wucherer, Michael (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Whole-body CT (wbCT) has been established as an internationally accepted diagnostic modality in multiple trauma. Until 2011, a uniform CT scanning protocol was used for all multiple trauma patients (pat.) at our hospital (OLD protocol = OP). In 2011, 2 new differently weighted protocols were introduced: TIME protocol (TP) for hemodynamically unstable pat. and DOSE protocol (DP) for pat. with stable vital parameters. The aim of this study was to compare the original “One-fits-all-concept” with the new, clinically oriented approach to wbCT.Materials and Methods This study retrospectively evaluated 3 distinct wbCT protocols, looking at automatic exposure control variation (AEC; OP/TP) and arm positioning close to the body/overhead (TP/DP). The analysis included waist circumference (WC, cm), injury severity score (ISS), examination time (ET, min), image noise (IN), and effective dose (E, mSv). Normality of distribution was assessed with the Kolmogorov-Smirnov test. Data are given as median and range. Test of significance with Kruskal-Wallis test or Mann-Whitney-U-test. Level of significance: 0.05.Results 308 pat. were included in the study (77 % m; age: 46 a, 18 – 90 a; WC: 93 cm, 66 – 145 cm). ISS was 14 (OP; n = 104; 0 – 75), 18 (TP; n = 102; 0 – 75) and 9 (DP; n = 102; 0 – 50). ET was 3.9 min (OP; 3.3 – 5.6 min), 4.1 min (TP; 2.8 – 7.2 min) and 7.7 min (DP; 6 – 10 min). IN showed no significant differences when comparing OP/TP but was significantly reduced in DP. For a wbCT (vertex to ischium), E could be reduced from 49.7 mSv to 35.4 mSv by optimizing AEC (OP/TP). Through the overhead repositioning of the arms in DP, a further reduction to 28.2 mSv was achieved.Conclusion AEC and arm repositioning have a crucial influence on image quality and dose. The presented clinical approach is superior to the original concept.Key Points:Citation FormatZiel Die Ganzkörper-CT (GKCT) ist als Primärdiagnostik in der Versorgung von schwerverletzten Patienten (Pat.) weltweit etabliert. Bis 2011 wurden alle Pat. in unserer Klinik mit dem ALT-Protokoll (AP) untersucht. Seit 2011 werden 2 different gewichtete Protokolle vorgehalten und adaptiert an den klinischen Zustand des Pat. eingesetzt. Bei instabilen Pat. wird das ZEIT-Protokoll (ZP) und bei kreislaufstabilen Pat. das DOSIS-Protokoll (DP) verwendet. Ziel dieser Studie war der Vergleich des alten „One-fits-all-Konzepts“ mit dem neuen, klinisch adaptierten Konzept.Material und Methoden Diese retrospektive Studie evaluiert 3 in Einzelaspekten differente GKCT-Protokolle: Differente Einstellung der Dosismodulation (DM, AP/ZP) und Armlagerung am Körper/über Kopf (ZP/DP). Evaluiert werden Bauchumfang (BU, cm), Injury-Severity-Score (ISS), Untersuchungszeit (UZ, min), Bildrauschen (BR) und effektive Dosis (E, mSv). Test auf Normalverteilung mittels Kolmogorov-Smirnov-Test. Angabe der Ergebnisse als Median und Spannweite. Signifikanzprüfung mittels Kruskal-Wallis- oder Mann-Whitney-U-Test. Signifikanzniveau: 0,05.Ergebnisse 308 Pat. erfüllten die Einschlusskriterien (77 % m; Alter: 46 a (18 – 90 a); BU: 93 cm (66 – 145 cm)). Der ISS lag bei 14 (AP; n = 104; 0 – 75), 18 (ZP; n = 102; 0 – 75) bzw. 9 Punkten (DP; n = 102; 0 – 50). Die UZ betrug 3,9 min (AP; 3,3 – 5,6 min), 4,1 min (ZP; 2,8 – 7,2 min) bzw. 7,7 min (DP; 6 – 10 min). Das BR zeigte im Vergleich AP/ZP keine signifikanten Unterschiede, lag beim DP jedoch signifikant niedriger. Für eine GKCT von Scheitel bis Sitzbein konnte im Vergleich AP/ZP durch Optimierung der DM E von 49,7 auf 35,4 mSv reduziert werden. Im Vergleich ZP/DP konnte durch die Armumlagerung über Kopf E auf 28,2 mSv weiter reduziert werden.Schlussfolgerung DM und Armlagerung haben entscheidenden Einfluss auf Dosis und Bildqualität. Das vorgestellte, klinisch adaptierte Konzept ist dem ursprünglichen „One-fits-all-Konzept“ überlegen.Kernaussagen: Zitierweise
Keywords: multiple trauma; whole-body CT; protocol optimization; arm positioning; dose reduction; clinically adapted approach